2010
DOI: 10.1007/s00425-010-1265-z
|View full text |Cite
|
Sign up to set email alerts
|

Salicylate-mediated suppression of jasmonate-responsive gene expression in Arabidopsis is targeted downstream of the jasmonate biosynthesis pathway

Abstract: Jasmonates (JAs) and salicylic acid (SA) are plant hormones that play pivotal roles in the regulation of induced defenses against microbial pathogens and insect herbivores. Their signaling pathways cross-communicate providing the plant with a regulatory potential to finely tune its defense response to the attacker(s) encountered. In Arabidopsis thaliana, SA strongly antagonizes the jasmonic acid (JA) signaling pathway, resulting in the downregulation of a large set of JA-responsive genes, including the marker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
140
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(155 citation statements)
references
References 66 publications
13
140
0
2
Order By: Relevance
“…expression of salicylic acid (SA)-responsive gene was inhibited by the higher expression of jasmonic acid (JA)-responsive gene, which was similar to the results of salicylate-mediated suppression of jasmonate-responsive gene expression in Arabidopsis(Leon-Reyes et al, 2010). Moreover, the relatively higher expression of LOX gene indicated the products encoded by the gene might involve in resistance response at ealy stage.…”
supporting
confidence: 73%
“…expression of salicylic acid (SA)-responsive gene was inhibited by the higher expression of jasmonic acid (JA)-responsive gene, which was similar to the results of salicylate-mediated suppression of jasmonate-responsive gene expression in Arabidopsis(Leon-Reyes et al, 2010). Moreover, the relatively higher expression of LOX gene indicated the products encoded by the gene might involve in resistance response at ealy stage.…”
supporting
confidence: 73%
“…Doares et al (1995) provided evidence that exogenous application of SA to tomato plants strongly inhibits the JA-induced expression of genes encoding PI I and II, suggesting that SA targets the JA pathway downstream of JA biosynthesis. Recently, Leon-Reyes et al (2010) showed that SA-mediated suppression of JA-responsive gene expression in Arabidopsis is targeted downstream of the jasmonate biosynthesis pathway. NPR1 and the TGA (for thymine, guanine, and adenine nucleotides) binding sequence protein family are important for the SA signaling pathway (Loake and Grant, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of JA responses can be regulated by antagonistic cross-talk with SA signaling (for review, Balbi and Devoto, 2008). In fact, SA can suppress the JAdependent response to wounding and pathogen or insect attack (Leon-Reyes et al, 2010).…”
Section: Salicylic Acidmentioning
confidence: 99%